PENERAPAN WORKPLACE SPIRITUALITY DI KBIH AN-NUR KARAH AGUNG SURABAYA - Mazidatus Sholikhah; Airlangga Bramayudha (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
Spirituality is an understanding related to the balance of one's soul both spiritually and materially. Spirituality is an effort to be close to God, then implemented in everyday life, including in the work environment. The application of Worplace Spirituality to employees can affect the quality of performance. In this study, the researchers found the following results: first, forms of implementing a spiritual workplace at KBIH An-Nur Karah Agung Surabaya, including: Dhuhur Prayer, Asar Prayer, Dhuha Prayer, Reading Al-Waqiah Letter, Saying Islamic sentences, Closing Aurot , and Listening to Murottal. Second, the factors supporting the implementation of spirituality workplace at KBIH An-Nur Karah Agung Surabaya, namely: facilities, sincerity, responsibility, mujalasah as-shalihin and physical evidence. While the inhibiting factors are: lack of time management skills.